1998
DOI: 10.1007/s004670050435
|View full text |Cite
|
Sign up to set email alerts
|

A model of sterile vesicoureteric reflux in the sheep

Abstract: Eighteen Coopworth ewe lambs were divided into three groups based on the initial cystourethrogram and cystometry findings at 5-7 weeks of age: group 1, 6 lambs with spontaneous low-pressure bilateral vesicoureteric reflux (VUR) on bladder filling were used to study the natural history of reflux; group 2, 5 lambs with no VUR detected were used to establish an experimental model of bilateral VUR using an unroofing surgical procedure; group 3, 7 lambs with spontaneous VUR detected during micturition had the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…As some of these morphological features could be non‐specific, they might be found in chronic allograft nephropathy. However, distal tubular dilatation has been found to be a specific histological feature during VUR, as demonstrated in experimental sheep kidneys (14). In our study, both proximal and distal tubules were found to be dilated in the biopsy tissues obtained from transplant patients with VUR.…”
Section: Discussionmentioning
confidence: 95%
“…As some of these morphological features could be non‐specific, they might be found in chronic allograft nephropathy. However, distal tubular dilatation has been found to be a specific histological feature during VUR, as demonstrated in experimental sheep kidneys (14). In our study, both proximal and distal tubules were found to be dilated in the biopsy tissues obtained from transplant patients with VUR.…”
Section: Discussionmentioning
confidence: 95%
“…The small bladders in these infants have urodynamic abnormalities with high voiding pressures. Sterile vesicoureteral reflux in the absence of elevated voiding pressures or bladder dysfunction does not produce renal damage (including scars) (17). Renal growth rates are unaffected by the initial severity or the persistence of vesicoureteral reflux, and no new renal scars develop after puberty (18).…”
mentioning
confidence: 99%